2017
DOI: 10.3390/catal7090258
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research of an Active Solution for Modeling In Situ Activating Selective Catalytic Reduction Catalyst

Abstract: Abstract:The effect of active solutions suitable for the in situ activation of selective catalytic reduction (SCR) catalysts was experimentally investigated using a designed in situ activation modeling device. To gain further insight, scanning electron microscopy (SEM), specific surface area analysis (BET), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and energy dispersive spectroscopy (EDS) analyses were used to investigate the effects of different reaction conditions on the chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…At the same time, the SCR catalysts in industrial application are facing many problems, such as high costs, poisoning and transformations. The steady increase of NO x emissions necessitates the improvement of abatement technologies [30]. In this context, the research on low-temperature SCR catalyst was launched.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the SCR catalysts in industrial application are facing many problems, such as high costs, poisoning and transformations. The steady increase of NO x emissions necessitates the improvement of abatement technologies [30]. In this context, the research on low-temperature SCR catalyst was launched.…”
Section: Introductionmentioning
confidence: 99%
“…When deactivation cannot be prevented, the regeneration of SCR catalysts is an interesting option. Ye et al successfully demonstrated that treatment of a deactivated vanadia-titania catalyst in a stationary SCR application with solutions containing a vanadia precursor and oxalic acid as well as a tungsta or molybdena precursor completely reactivated the used catalyst [7].…”
mentioning
confidence: 99%